ANALISIS KURIKULUM MATEMATIKA SMA DI INDONESIA DAN FINLANDIA: PENDEKATAN PEMBELAJARAN DAN DAMPAKNYA TERHADAP KOMPETENSI SISWA - Suci Mustika Sari; Santika Lya Diah Pramesti (PHI: Jurnal Pendidikan Matematika, 2026)
This study was motivated by the differences in high school mathematics curricula across various countries, which influence teaching approaches and student competencies. Indonesia and Finland have distinct characteristics in their mathematics curricula, particularly in terms of learning objectives, content organization, and the teaching strategies employed. This study aims to analyze the high school mathematics curricula in Indonesia and Finland, specifically focusing on the teaching approaches used and their impact on student competencies. The research method employed is a Systematic Literature Review (SLR), involving the examination of various journals, scientific articles, and relevant academic sources regarding mathematics curricula in both countries. The results indicate that the mathematics curriculum in Finland places greater emphasis on conceptual understanding, contextual learning, and the development of critical thinking and problem-solving skills. Meanwhile, the mathematics curriculum in Indonesia tends to be oriented toward mastery of subject matter, achievement of curriculum targets, and academic evaluation. These differing approaches impact student competencies, particularly in higher-order thinking skills, creativity, and mathematical problem-solving. This study is expected to serve as a reference in the development of mathematics curricula in Indonesia to make them more adaptive, effective, and oriented toward the development of student competencies.